Pediatric collections. (Pediatric collections., 2018)
The opioid crisis has become far more serious than some of the other epidemics the country has faced. Patients are being prescribed opioids for pain too often and for too long, with insufficient oversight in terms of administering the drug, which can lead to abuse. In addition, if an adult is prescribed 30 days of opioids but uses the medication for only two days, the rest of it may sit in a medicine cabinet. If a teen has access to the leftovers, there is potential for abuse. So, what alternatives to opioids are available to pediatricians caring for patients in pain? This collection of timely.